EXPERIMENTAL SNOW PLENUM AIR COOLING SYSTEM FOR BYRD STATION, ANTARCTICA. - Hoffman,C. R. (1966)
Since mechanical refrigeration is beyond economic consideration, tunnel cooling systems for Byrd Station, Antarctica, are dependent on the utilization of the immense heat sink represented by the snowfield on which the camp is built. A system has been proposed which would draw surface air through porous cold snow into an undersnow plenum and deliver the cooled air to inhabited tunnels. (Author)